PENGARUH PENGGUNAAN INTERNET TERHADAP PENYELASAIAN TUGAS (PR) MAHASISWA UNIVERSITAS QUALITY PROGRAM STUDI PGSD PADA MATA KULIAH KONSEP DASAR IPA - Hotma Tiolina Siregar (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This study aims to determine the effect of internet use on task completion (PR) of PGSD University Quality Study Program Students in Science Concept Basic Subjects 2019/2020 Academic Year. This type of research is expostfacto with quantitative methods. The results of the average value obtained by the class 2B11 82.74 namely the class that uses the Internet for completing assignments and class 2B12 74.05 ie the class that does not use the internet for task completion. Table frequency of final grade test scores that use the internet for completing assignments and classes that do not use internet for completing assignments can be distributed in a relative frequency table then drawn into a histogram to determine the comparison of students completing assignments using the internet and students completing assignments not using Internet. Hypothesis testing using t test with a significant level of α = 0.05 and dk = (obtained 36.68 (0.975) (76) = 1.73. From the results of hypothesis testing the data can be concluded that there is an effect of task completion on task completion (PR) Quality University Students PGSD Study Program in Science Basic Concept Courses.Keywords: Task Completion, Internet Usage, Expostfacto